Entrepreneurial solutionism, characteristic cultural industries and the Chinese dream - Keane, Michael; Chen, Y. (Routledge, 2017)
In this paper, we chart the development of creative cities from urban clusters through to ‘characteristic towns’, the latter typology reflecting a government desire to build distinctive cultural brands. We illustrate how this recent development iteration has played out in Hangzhou and its relationship to Internet+, a policy blueprint introduced by the Chinese government in March 2015 which underpins ambitions to make China an innovative nation. The term ‘entrepreneurial solutionism’ describes a proclivity to see digital technology as a solution to China’s social and economic problems, and a way to enhance the realisation of the ‘Chinese Dream’ of national rejuvenation. Central to the Internet + blueprint is the slogan ‘mass entrepreneurship, mass innovation’, suggesting elements of the kind of Silicon Valley style neoliberalism, often celebrated in start-up cultures. While it has become fashionable to append the term neoliberalism to China’s developments, we argue that China’s reversion to hard authoritarianism under Xi Jinping renders this description problematic.